ABO histo-blood group and risk of respiratory atopy in children: a review of published evidence - Uwaezuoke SN; Eze JN; Ayuk AC; Ndu IK (Dove Medical Press, 2018)
Samuel N Uwaezuoke,1 Joy N Eze,1 Adaeze C Ayuk,1 Ikenna K Ndu2 1Department of Paediatrics, University of Nigeria Teaching Hospital (UNTH), Ituku-Ozalla Enugu, Nigeria; 2Department of Paediatrics, Enugu State University Teaching Hospital, Enugu, Nigeria Abstract: Besides their fundamental role in transfusion medicine, ABO and other histo-blood group antigens are associated with the pathogenesis of some human diseases such as malignancy and thrombosis. Reports also show a possible relationship with the risk of asthma and other forms of respiratory atopy. This paper aims to critically review the current evidence linking ABO histo-blood group with the risk of respiratory atopy in children and adults. A literature search was conducted with PubMed to gather baseline data about this relationship. The search extended to studies published within the past 45 years. First, the molecular mechanism underpinning the role of ABO antigenic system in human diseases comprises a fascinating relationship with von Willebrand factor and several pro-inflammatory and adhesion molecules. Second, specific blood group types vary with asthma phenotypes; severe asthma is associated with B phenotype, while mild and moderate asthma is associated with O and A phenotypes. Third, O phenotype has been linked to allergic rhinitis but only in males. Furthermore, asthma risk is related to O/Lewis negative/secretor phenotypes, while a significant relationship has also been established with B phenotype but not with A and O phenotypes. However, one study failed to establish a significant relationship with any of the ABO blood group antigens. In conclusion, there is no unanimity on the specific histo-blood groups linked to respiratory atopy risk, although asthma phenotypes are associated with specific blood groups. Despite the prospect that this relationship holds for the use of blood-group typing in evaluating respiratory atopy risk in children, more evidence-based studies are still required for its validation. Keywords: blood-group phenotypes, asthma phenotypes, B phenotype, von Willebrand factor, asthma risk, blood-group typing